2015
DOI: 10.1146/annurev-orgpsych-032414-111341
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Stress Management Interventions and Health Promotion

Abstract: Employee health and wellness are important for employees, their families, and their organizations. We review the literature on both stress management interventions in organizations and workplace health promotion and wellness programs, from the lens of primary, secondary, and tertiary interventions as well as the framework provided by the job demands-resources model (Bakker & Demerouti 2007). Stress management interventions tend to be ameliorative, often focusing on restoring resources that have been depleted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
128
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 46 publications
1
128
0
8
Order By: Relevance
“…First, our SMI did not include organizational-level measures. It has been suggested that SMI in the workplace combining both organizational and individual levels might be more effective [1]. Thus, our results may have underestimated the potential benefits.…”
Section: Tablementioning
confidence: 79%
See 2 more Smart Citations
“…First, our SMI did not include organizational-level measures. It has been suggested that SMI in the workplace combining both organizational and individual levels might be more effective [1]. Thus, our results may have underestimated the potential benefits.…”
Section: Tablementioning
confidence: 79%
“…Consequently, stress management interventions (SMI) in the workplace have received increasing attention from researchers as well as employers and employees [1]. Generally, SMI at the individual level with the largest effects on mental health are based on psychotherapeutic principles, mostly cognitive-behavioral therapy and psychodynamic therapy.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such research would be highly relevant to clinical practice, highlighting the role of work stress in the accumulation of adversities across the life course and CR. Finally, interventions in the workplace that aim at reducing work stress at each period of the lifespan and disease development are warranted, i.e., focusing not only on primary prevention but also on secondary/tertiary prevention 41) .…”
Section: Step 4: Work Stress Increases the Risk Of Recurrent Cvd In Wmentioning
confidence: 99%
“…Programs that focus on proactively addressing PPWB factors rather than addressing them reactively can have a significant impact on the critical elements of a successful high performing organization (including engagement, productivity and safety). Further, there is growing evidence that organizational interventions, especially when combined with individuallevel interventions, can be quite effective in promoting a positive, healthy work environment (Tetrick and Winslow, 2015). The case studies described here demonstrate the inter-relatedness of stress, health and safety.…”
Section: Discussionmentioning
confidence: 77%